Effects Of Crushing on Cutting and Cleaning of Surface Facilities in Cutting and Processing of Polymer Materials - Fayzimatov Shukhrat Nomonovich; Ergashev Ilhomjon Olimjonovich; Valikhonov Dostonbek Azim o’g’li (Genius Journals, 2022)
This article is about cutting and polishing polymeric materials. Prepared on the nature of cutting modes during cutting and the effect of cutting modes on surface cleanliness.
Keywords: Polymer; shavings; roughness; cutter